2015
DOI: 10.1111/head.12732
|View full text |Cite
|
Sign up to set email alerts
|

Memantine for Prophylactic Treatment of Migraine Without Aura: A Randomized Double‐Blind Placebo‐Controlled Study

Abstract: Memantine might be a tolerable and efficacious option for prophylaxis in patients with migraine without aura. Tolerability, short duration required for titration, and safety profile in pregnancy might give memantine an advantage over other antimigraine medications. The study was registered in the Iranian Registry of Clinical Trials (Registration number: IRCT2013120115616N1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 21 publications
0
71
1
5
Order By: Relevance
“…In some protocols, a headache diary provided a qualitative method to evaluate pain level, classified as (i) mild; (ii) moderate; or (iii) severe pain . Other studies used pain intensity scales to rate pain level using 0‐10 scales . We believe that analysis by mean ± SD (performed in the studies) should not be the most sensitive and appropriate way to evaluate the pain level measured by qualitative methods.…”
Section: Discussionmentioning
confidence: 99%
“…In some protocols, a headache diary provided a qualitative method to evaluate pain level, classified as (i) mild; (ii) moderate; or (iii) severe pain . Other studies used pain intensity scales to rate pain level using 0‐10 scales . We believe that analysis by mean ± SD (performed in the studies) should not be the most sensitive and appropriate way to evaluate the pain level measured by qualitative methods.…”
Section: Discussionmentioning
confidence: 99%
“…Memantine inhibits cortical spreading depolarization in animal models [50]. Two observational studies [128,129] and one randomized, double-blind, placebo-controlled study [130] have reported efficacy of memantine as a migraine preventive therapy. It is not approved for migraine prevention.…”
Section: Memantinementioning
confidence: 99%
“…The potential efficacy of memantine for the treatment of migraine has been tested clinically including in open‐label pilot studies, a case series, and most recently a randomized placebo‐controlled trial, which taken together suggest effectiveness (Bigal, Rapoport, Sheftell, Tepper, & Tepper, ; Cammarata & Krusz, ; Charles, Flippen, Romero Reyes, & Brennan, ; Kew & Kemp, ; Noruzzadeh et al., ; Spengos, Theleritis, & Paparrigopoulos, ). Memantine is generally well tolerated because of its relatively fast channel off‐rate and partial untrapping (Parsons et al., ).…”
Section: Introductionmentioning
confidence: 99%